Establishing a Regional-Owned Limited Liability Company: Would it Support an Integrated Tourism Management in Bali? - Luh Ayu Nadira Saraswati; Anak Agung Gede Duwira Hadi Santosa (Udayana Journal of Law and Culture, 2021)
The rapid development of tourism in Bali has made this sector becomes the main pillar of the economy. Facts indicate that the tourism industry in Bali is not parallel with the equal distribution, which entails an imbalance in both tourism facilities and tourism management. This has an impact on chaotic tourism management: many tourist destinations and attractions were not managed properly and could not develop their potency optimally. This situation reflects an urgency to conceive an integrated tourism development and management. The Bali Provincial Government has addressed this issue by launching the concept of One Island One Management. This paper aims to analyze the tourism management arrangements in Bali with the various challenges faced in its application and to assess the establishment of Regional-Owned Limited Liability Company in realizing the concept of an integrated tourism management in Bali. In terms of writing methodology, this paper applies a normative legal research. The result suggested that a regional-owned limited liability company (LLC) can support the realization of an integrated tourism management in Bali. From a legal perspective, a regional-owned LLC is subject to the company law, which entails that it will strengthen the professionalism in managerial aspects and also will accommodate the participation of the region through the shareholder forum.